Production of Bioactive Recombinant Reteplase by Virus-Based Transient Expression System in Nicotiana benthamiana - Ma, Ting; Li, Zhiying; Wang, Sheng (Frontiers in Plant Science, 2019)
To explore a cost-effective alternative method to produce the recombinant thrombolytic drug Reteplase (rPA), a plant viral amplicon-based gene expression system was employed to transiently express bioactive Strep II-tagged recombinant rPA in Nicotiana benthamiana leaves using agroinfiltration. Several gene expression cassettes were designed, synthesized in vitro, and then cloned into Tobacco mosaic virus (TMV) RNA-based overexpression vector (TRBO). Codon optimization, subcellular targeting, and the effect of attached Strep-tag II were assessed to identify conditions that maximized expression levels of the recombinant rPA in tobacco leaves. We found that codon optimized rPA with N-terminal Strep-tag II that was targeted to the endoplasmic reticulum (ER) provided the highest amount of biologically active protein; i.e. up to 50 mg from per kilogram fresh weight leaf biomass in less than one week. Furthermore, the recombinant rPA was conveniently purified from inoculated leaf extracts by a one-step purification procedure via the Strep-tag II. The plant-made rPA was glycosylated with molecular mass of 45.0 kDa and its in vitro fibrinolysis activity was equivalent to the commercial available rPA. These results indicate that the plant viral amplicon-based system offers a simple and highly effective approach for cost-effective large-scale production of recombinant rPA.